Multimodality in language education: implications of a multimodal affective perspective in foreign language teaching - Guo, Xiaoshuang (Frontiers in Psychology, 2023)
Foreign language learners often confront various emotional challenges within academic environments, impeding their progress in developing literacy skills. Consequently, effective language instruction should encompass teaching approaches that acknowledge the emotional requirements of students. To address this, we propose a multimodal affective methodology capable of evaluating emotions in foreign language education scenarios. Moreover, this methodology holds the potential to elucidate the pedagogic contributions of a wide array of emotional variables to academic outcomes.Guided by this multimodal affective analysis methodology, this study uses German as a foreign language (GFL) learning as an example to delve into the realm of improving writing proficiency. It probes into the effects of integrating multimodal corrective feedback (MCF) on academic writing exercises. To achieve so, this study explores modalities suitable for analyzing emotion in academic writing practices. Furthermore, it delves into how the choice of corrective feedback mode intricately influences the nature of feedback itself and subsequently influences students' emotional responses. Through a comprehensive exploration of the interplay between distinct modes of delivering feedback and their impacts on learners' engagement, this investigation strives to decode the intricate dynamics of emotions that underscore language acquisition. With these insights, this study discusses how teachers can improve their teaching strategies by combining changes in learners' emotional states and providing emotional support.